2015
DOI: 10.15294/kemas.v11i1.3401
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Media Film Terhadap Sikap Ibu Pada Deteksi Dini Kanker Serviks

Abstract: <p>Salah satu cara yang praktis dan murah untuk mencegah terjadinya kanker serviks adalah melalui tes Inspeksi Visual Asam Asetat (IVA). Upaya untuk mempengaruhi sikap ibu pada tes IVA adalah pendidikan kesehatan melalui film. Tujuan penelitian ini adalah untuk mengetahui pengaruh pendidikan kesehatan melalui film terhadap sikap ibu pada tes IVA. Penelitian ini dilakukan pada tahun 2014. Rancangan penelitian ini adalah non randomized within group design. Pengambilan sampel dilakukan dengan teknik consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
6
0
5
Order By: Relevance
“…Attitude is an evaluative bias towards a stimulus or object that has an impact on how someone is dealing with that object. According to Fishbein in Mulyati, et al (2015) attitude is affective responses or judgments of someone's positivity towards an object. Attitude originates from beliefs about behavior (behavioral beliefs) and one's evaluation of the consequences to be borne (Montano, 2008in Mulyati, 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Attitude is an evaluative bias towards a stimulus or object that has an impact on how someone is dealing with that object. According to Fishbein in Mulyati, et al (2015) attitude is affective responses or judgments of someone's positivity towards an object. Attitude originates from beliefs about behavior (behavioral beliefs) and one's evaluation of the consequences to be borne (Montano, 2008in Mulyati, 2015.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study indicated the existence of conformity with some previous studies. [13][14] Health promotion activities aimed at predisposing factors are in the form of providing information due to lack of knowledge, information, description, and awareness-raising notification. The purpose of this health promotion activity can provide or increase someone's knowledge, in this case, it is the knowledge of cervical cancer and early detection efforts through the IVA method.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in knowledge and attitude score in the intervention group was higher than in the control group. Mulyati (2015) found that health education had a positive impact on mothers' attitude from the increased median attitude score from 44.23 to 78.85. Yu (2015) found a positive correlation between counseling and attitude change towards health among students.…”
Section: Methodsmentioning
confidence: 97%